2021
DOI: 10.4136/ambi-agua.2686
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of 17α-ethinylestradiol in Paranoá Lake watershed (Brasília, Brazil): sewage, freshwater and treated water

Abstract: Emerging contaminants such as 17α-ethynylestradiol (EE2) can be discharged from sewage systems and contaminate water supplies. Paranoá Lake is a strategic water reservoir in Brasília (Brazil) that receives treated sewage from sewage treatment plants (STPs) and has recently become a water supply. This study monitored EE2 residues in different matrices from Paranoá Lake watershed using the ELISA method. This monitoring was performed together with the local environmental agency in two periods. EE2 was detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
5
0
3
Order By: Relevance
“…A redução de seu consumo em 2020 e 2021 se justifica pela priorização das unidades de saúde no atendimento de casos graves de COVID e de síndrome respiratória aguda-grave (SRAG) 46 , apesar de não ter havido desabastecimento durante esse período. Neste trabalho, estamos considerando a farmacocinética somente do 17α-etinilestradiol, pois diversos autores vêm apontando seus efeitos deletérios na biota selvagem aquática 17,36,47,48 , o que justifica seu baixo valor de PNEC (0,000035 μg/L). Esse fármaco foi incluído neste estudo como parâmetro de comparação do seu risco ambiental estimado em relação aos demais fármacos 49 .…”
Section: Consumo De Medicamentosunclassified
See 2 more Smart Citations
“…A redução de seu consumo em 2020 e 2021 se justifica pela priorização das unidades de saúde no atendimento de casos graves de COVID e de síndrome respiratória aguda-grave (SRAG) 46 , apesar de não ter havido desabastecimento durante esse período. Neste trabalho, estamos considerando a farmacocinética somente do 17α-etinilestradiol, pois diversos autores vêm apontando seus efeitos deletérios na biota selvagem aquática 17,36,47,48 , o que justifica seu baixo valor de PNEC (0,000035 μg/L). Esse fármaco foi incluído neste estudo como parâmetro de comparação do seu risco ambiental estimado em relação aos demais fármacos 49 .…”
Section: Consumo De Medicamentosunclassified
“…A Tabela 2 mostra a quantidade de cada medicamento diariamente excretada pela urina (QFexc) e sua concentração estimada no esgoto (PECest). Como efeito de comparação, foi realizada uma revisão da literatura sobre os valores de PEC desses seis fármacos 17,[59][60][61][62] .…”
Section: Excreção De Medicamentos E Risco Ambientalunclassified
See 1 more Smart Citation
“…Notably, there was no supply shortage during this period. Our study considered only the pharmacokinetics of 17α-ethinylestradiol, given that several studies have reported its harmful effects on wild aquatic biota 17,36,47,48 , which would explain its low PNEC value (0.000035 μg/L). This drug was included in our study as a parameter for comparing its estimated environmental risk with respect to the other drugs 49 .…”
Section: Consumption Of Medicationmentioning
confidence: 99%
“…These compounds are called emerging contaminants, and there are no regulations regarding their environmental threats 17 . The effects can be observed in very low concentrations (ng/L) and in various aquatic species [18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%